plz tell me how this came..
this firat line
Attachments:
![](https://hi-static.z-dn.net/files/d3f/41737fb4b0523f5a7a47cde234a0de1a.jpg)
Answers
Answered by
0
Let consider the both polynomial as alpha and beta
So that eq came because
F(x)=x^2+px+45
Put
Here
(Alpha-beta)^2-4alpha beta =45
Because
Sum=alpha +beta
And polynomial =-p
So we take these equation
Hope you like my ans
nsnznznz:
not understanding
Answered by
2
Explanation:
= F (x) = x^2 + Px + 45
Now , Alpha Beta ^2 - 4 Alpha Beta = 45
Polynomial = P
Similar questions